Die hämocytären Abwehrreaktionen des Blutes von Strongylogaster xanthoceros (Stephens) und Strongylogaster lineata (Christ) gegen die endoparasitische Ichneumonide Mesoleius niger (Gravenhorst) (Hymenoptera: Tenthredinidae und Ichneumonidae). - Adam, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1966)
This study deals with problems of the defensive reactions of insect blood against endo-parasitic species of insects. - It shows that also in its normal host the parasite meets with vigorous defensive reactions. The parasite eggs invading the body of the host larva are coated with dense layers of blood cells which form melanin and thus eventually produce a compact and impenetrable capsule that impedes the embryonic development of the parasite. This interruption of the exchange of substances between the parasite egg and the hemolymph of the host is regarded as the real cause of its death. The following rules are established for the result of the parasitisation: The survival of the parasite egg requires an optimum degree of development at oviposition. The effectiveness of the defensive reactions depends on the quantitative variations in the number of hematocytes and the qualitative changes of the hemolymph connected with them, especially with regard to the phagocytic types of hematocytes. It appears that the moulting phases offer the most favourable conditions for successful parasitising, while the defensive reactions of the host are strongest in the periods with the greatest number of hematocytes.